The Effectiveness of Google Classroom as an Alternative Online Learning Media - Sofyan Hadinata; Didik Himmawan; Syarif Maulana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Google Classroom is one of the educational features provided by Google Apps For Education (GAFE) which was released to the public on August 12, 2014. On the Google Classroom website it is also written that Google Classroom is connected to all other Google for Education services, so that educators can utilize Google Mail, Google Drive, Google Calendar, Google Docs, Google Sheets, Google Slides, and Google Sites in their learning process. Knowing the Effectiveness of Google Classroom as an Alternative Online Learning Media. This study uses data collection with a qualitative-descriptive library research method, namely research that focuses on the literature that is the object of study. This study aims to provide information about the effectiveness of Google Classroom as an alternative learning media. In the current 4.0 era that utilizes communication technology as a means of life, including in the world of education that utilizes communication technology as a learning medium. The results of the discussion say that Google Classroom is very effective for learning and can be used as an alternative online learning media when face-to-face/offline learning cannot be carried out. This is because Google Classroom is internet-based and easily accessible, making it easy for anyone to use. This makes it much easier for teachers and students to continue learning when face-to-face meetings are not available and offers greater flexibility.